Improving Deep Brain Stimulation Electrode Performance in vivo Through Use of Conductive Hydrogel Coatings - Hyakumura, Tomoko; Aregueta-Robles, Ulises; Duan, Wenlu; Villalobos, Joel; Adams, Wendy K.; Poole-Warren, Laura; Fallon, James B. (Frontiers in Neuroscience, 2021)
Active implantable neurological devices like deep brain stimulators have been used over the past few decades to treat movement disorders such as those in people with Parkinson’s disease and more recently, in psychiatric conditions like obsessive compulsive disorder. Electrode-tissue interfaces that support safe and effective targeting of specific brain regions are critical to success of these devices. Development of directional electrodes that activate smaller volumes of brain tissue requires electrodes to operate safely with higher charge densities. Coatings such as conductive hydrogels (CHs) provide lower impedances and higher charge injection limits than standard platinum electrodes and support safer application of smaller electrode sizes. The aim of this study was to examine the chronic in vivo performance of a new CH coating that supports higher safe charge densities than traditional platinum electrodes. Two different formulations of CH were tested in vitro for their electrochemical performance and stability during insertion into a model brain, and the formulation with lower swelling characteristics was chosen for the in vivo study. CH-coated or uncoated Pt electrode arrays were implanted into the brains of 14 rats, and their electrochemical performance was tested weekly for 8 weeks. Tissue response and neural survival was assessed histologically following electrode array removal. CH coating resulted in significantly lower voltage transient impedance, higher charge injection limit, lower electrochemical impedance spectroscopy, and higher charge storage capacity compared to uncoated Pt electrodes in vivo, and this advantage was maintained over the 8-week implantation. There was no significant difference in evoked potential thresholds, signal-to-noise ratio, tissue response or neural survival between CH-coated and uncoated Pt groups. The significant electrochemical advantage and stability of CH coating in the brain supports the suitability of this coating technology for use in smaller, higher fidelity electrode arrays with higher charge density requirement.